(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Research results show that the prevention of tumor diseases, their early diagnosis, and uncomplicated treatment are of great importance. However, one of the most serious problems in these pathologies is their primary detection. One of the systems sensitive to pre-pathological conditions in the body is the immune system, whose cellular and humoral factors react with quantitative and qualitative changes to the ongoing pre-pathological states in the body, which occur asymptomatically and without external clinical manifestations. It has been shown that quantitative changes in these factors indicate pre-disease states of the body.